HISTORAL DEVELOPMENT OF THE CONCEPT OF HIGHER EDUCATION AND ITS VALUES - Tinfavičienė, Ingrida (Acta Paedagogica Vilnensia, 2007)
The aim of the article is to present the most important aspects of historical development of higher education and to look at the context of the origin of basic features of higher education. The most scientists agree that the main features of university, such as academic freedom, autonomy, democracy, should be preserved despite of globalization challenges. The article starts with the idea of higher education in antiquity, and then discusses concepts of higher education in the works of Humboldt, Schleiemacher, and Newman. Next chapter of the article presents conceptions on higher education in the understanding of Flexner, Gasset, Lewis, Hutchins, Jaspers, Oakshott, Minogue and Barnett. The main ideas on higher education at university started from G. Fichte (1808) concluded with R. Barnett (1990) are presented in the table. The third part of the article describes the situation in Lithuanian higher education system and shortly presents the main challenges of massification, diversification and internationalization in the country. The article concludes that, in continuing the democratic tradition of higher education, modern universities preserve common values, aims and ideas, and the concept of modern higher education should be based on the presumption that higher education has to be developed as an autonomous institution of science and learning, which is free from external pressure or control by other institutions. Lectors take a critical position with regard to the knowledge they deliver to students and include students in scientific research process, thus contributing to their critical thinking and intellectual power. The relationships among members of academic community are based on a parity basis and each of them is entitled to academic freedom.